Análisis del acto docente en la práctica pedagógica presencial en el programa de administración de empresas en la Universidad de la Costa en el 2013 (2013)
This research is necessary because teacher evaluation highlighted within their training and professional performance and the University would be strengthened as a driver of continuous improvement of the educational act. Research is necessary because the act of teaching in their teaching practices to identify the strengths and needs of the teacher and thus establish, coping strategies. Society demands an education system that meets their needs from their teachers maintaining an optimal level in the management of knowledge generated within and outside the educational environment, which is possible if there is a methodological assessment that integrates strategies including teaching and ways to evaluate teachers utilizing taking exercise as part of a process and not a disqualifying event of teaching. The results of the descriptive level research would provide the ability to detect aspects of pedagogical practice that takes place in the CUC and determine if they are appropriate to their educational model. This research would provide methodological contributions that would serve as an educational exercise evaluative parameters to other institutions that would like to apply the methodological structure designed. The technique of systematic observation of teaching practice, the tools developed and the way of presenting the results could provide guidance to other similar studies in other higher educational institutions. Would benefit not only methodological but theoretical benefits to the extent that the educational community could have a consultation paper prepared under the guidelines of the scientific method authorized concepts arising from different theoretical constructs and contemporary trends. Present the institutional pedagogical model used as the basis for other institutions to formulate its own institutional model. Teachers in the University would be of much use since it could help improve teaching practice, while giving them the opportunity to express their views, and could identify their strengths and weaknesses and from them generate a plan action that may lead to its improvement, training and development to help raise their professional level. Students would be of benefit because it would identify through their teachers new ways to access knowledge. The CUC as an institution and in particular to the people who run their formation processes because obtained through a record of the results of the pedagogical activity of teachers who integrate enabling implement new measures in relation to the pursuit of quality in the processes integral formation of students. In short, can count on, with a full and detailed information about the methodologies employed by faculty that integrates. It is considered one of the main contributions is the design and implementation of a measurement instrument teacher pedagogical act, to the descriptive level research permits. It is interesting to pedagogy, set in one quantitative and qualitative research in a complementary and not exclusive as traditionally conceived. Being a process research contributes to the understanding of meaning and transformation of pedagogical practice, it is important that a line of research tends to value and demand a paradigm coherence, is to provide the parameters needed to transform a reality or problematic exists. Failure to perform this investigation to describe the act of teaching from teaching practice Coast University would lack reliable tools to demonstrate what professional profiles of teachers and COAST UNIVERSITY which used to lead skills and impart pedagogical processes higher education quality and equity, so, managers have no way to know with precision which gives the scientific method, the level of quality of its teachers teaching act. It would ignore the study of an important variable in the qualification process must advance pedagogical university under the accreditation process has been experiencing in recent years, an issue that was also highlighted in different visits to the institution by peer reviewers sent by the national accreditation council. The affected teachers would also not have access to scientific systematic feedback through the activity they perform, and would be less likely to improve their pedagogical practice, the students would not get in an organized and planned new guidelines to facilitate their access to knowledge. The thoughts and ideas expressed are their delimitation and we note that in terms Delimitation Population: As under study establishes the body active undergraduate teaching at the University of Costa properly linked in the first quarter of 2013. Space Delimitation: The study was conducted in the University's educational environments. Temporal Delimitation: The design of this research is aimed to develop in the first quarter of 2013.